The application of intelligent piano teaching in college education/ Liu Chang, Md Jais Ismail and Wang Hai Ying - Chang, Liu; Ismail, Md Jais; Ying, Wang Hai (Universiti Teknologi MARA, Perak, 2023)
With the advent of the age of artificial intelligence, intelligent music education is also developing rapidly. The intelligent piano is an intelligent product that combines conventional piano technology with the latest computer network technology, which indicates that piano learning technology has entered the age of intelligence. The purpose of this study is to explore the advantages of intelligent pianos, verify the effectiveness of intelligent pianos for piano skill improvement, and to investigate how to use intelligent pianos in combination with the intelligent features they offer for piano teaching to college students. Using a quasi-experimental research design, this paper provides a quantitative analysis by comparing the learning of two groups of students in different teaching, and pointed out the difference in performance between the two groups of students. The strengths and significance of intelligent piano teaching are further discussed with some recommendations for future studies.